If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -7) + 3x = -3 Reorder the terms: 3(-7 + x) + 3x = -3 (-7 * 3 + x * 3) + 3x = -3 (-21 + 3x) + 3x = -3 Combine like terms: 3x + 3x = 6x -21 + 6x = -3 Solving -21 + 6x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 6x = -3 + 21 Combine like terms: -21 + 21 = 0 0 + 6x = -3 + 21 6x = -3 + 21 Combine like terms: -3 + 21 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| (4-2y)+3y=-1 | | 2(x-6)-3x=-2 | | -56x+45z^2-45=0 | | 5(t-4)+5t=5(2t+4)-11 | | 6(k-7)=9(k) | | 0.4(x+50)+0.8=56 | | A=1/3zks | | 4+6n-3=4n+17-2n | | 6x^2=54x+36-0 | | 7l^2-274l-440=0 | | 7=20-16x^2 | | 37/6= | | F(x)=3x^2+5x-6 | | 18(t-3)+3t=7(3t+3)-10 | | V-b=5 | | 0.30x+0.05(12-x)=0.10(21) | | 0.5x-1.1=3.6x+2.3 | | 72y=180 | | y+72y=180 | | 0=1296-.36x^2 | | 2(x+6)=24 | | (x+16)=(4x-29) | | 40/64 | | 60/98 | | 3+5x=x+11 | | (1/5)q=9-(2-5)q | | (x+19)=(3x-21) | | 3x+18=12x | | 7a^2+10a+2=0 | | x^2+y^2-7x-2y=0 | | (x-3)*(x+3)-x*(x-4)=1 | | 6x(x+2)=-5x-5 |